Identifikasi Permasalahan Mahasiswa Evaluasi Semester Program Akademik dan Vokasi di Institut Teknologi Sepuluh Nopember Surabaya - Purwanto, Yuli; Setiawan, Setiawan; Sunawi, Sunawi; Iman Nurdjati, Fatkhul; Machmudah, Siti (JURNAL SOSIAL HUMANIORA (JSH), 2024)
This study investigates the issues faced by students with Dispensation, Probation Semester Promotion, and Non-Promotion statuses based on evaluations from the 2021 Even Semester to the 2024 Odd Semester at Institut Teknologi Sepuluh Nopember, Surabaya. Using a quantitative descriptive approach, the research examines problems in semester evaluations. The population consists of 422 active students, with a sample of 252 students selected through Proportioned Stratified Random Sampling. Data was collected via questionnaires and interviews. Analysis employed the Guidance and Counseling Problem Checklist (DCM) in Higher Education, covering 11 topics through 56 Likert-scale statements. Problems were ranked based on Respondent Achievement Level (TCR) percentages. Findings reveal that the most significant issue is in the "Very Problematic" category. The top problem topic is Campus Adjustment (69.78%), with the leading issue being motivation to study (88.73%). The second issue is Future and Ambition (55.94%), with a focus on identifying self-potential (79.60%). Social Life and Organizational Activity ranks third (52.56%), primarily due to lack of organizational participation (60.79%). Lastly, Recreation and Hobbies (51.40%) highlights insufficient time for hobbies to boost enthusiasm (65.56%). These findings underscore key areas for student support interventions.